Skin Manifestations in Patients with Adult-onset Immunodeficiency due to Anti-interferon-gamma Autoantibody: A Relationship with Systemic Infections - Kamonwan Jutivorakool; Prattana Sittiwattanawong; Kornphaka Kantikosum; Cameron P. Hurst; Chanat Kumtornrut; Pravit Asawanonda; Jettanong Klaewsongkram; Pawinee Rerknimitr (Medical Journals Sweden, 2018)
Adult-onset immunodeficiency due to anti-interferon-γ autoantibody is an emerging acquired immunodeficiency with frequent skin manifestations. A retrospective chart review was conducted and identified 41 patients with the syndrome. Skin involvement was detected in 33 (80%) patients, 15 (45%) with infective skin diseases and 27 (82%) with reactive skin disorders. Reactive lesions were mostly neutrophilic dermatoses, e.g. Sweet syndrome. Of note, the presence of neutrophilic dermatoses was highly associated with infections of other sites. An adjusted odds ratio for the existence of infections in patients with neutrophilic dermatoses was 14.79 (95% CI: 5.13, 42.70; p < 0.001). Moreover, neutrophilic dermatoses were significantly correlated with opportunistic infections observed in those with defects in cell-mediated immunity including non-tuberculous mycobacterium and disseminated fungal infection. The odds ratio for opportunistic infections in the presence of neutrophilic dermatoses was 12.35 (95% CI: 5.00, 30.55; p < 0.001). Thus, the presence of neutrophilic dermatoses in patients with the syndrome can signal opportunistic infections that warrant physician attention.